2019
DOI: 10.1111/bph.14816
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds as potential adjuvants to cancer therapy: Preclinical evidence

Abstract: Traditional chemotherapy is being considered due to hindrances caused by systemic toxicity. Currently, the administration of multiple chemotherapeutic drugs with different biochemical/molecular targets, known as combination chemotherapy, has attained numerous benefits like efficacy enhancement and amelioration of adverse effects that has been broadly applied to various cancer types. Additionally, seeking natural‐based alternatives with less toxicity has become more important. Experimental evidence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
175
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(211 citation statements)
references
References 104 publications
(113 reference statements)
1
175
0
Order By: Relevance
“…Furthermore, in recent decades, a significant number of medicinal herbs have been reported to have biofunctional effects in treating chronic liver diseases through eliminating viruses, alleviating fibrogenesis, and suppressing tumorigenesis. As a result, plant extracts can be considered as potential anti-cancer candidates for cancer therapy [ 9 , 10 ]. Here, in the first study to investigate the anti-hepatoma activity of CAt extract in vitro and in vivo, our results first found that HCC cells were inhibited by CAt extract; nevertheless, the cytotoxicity of CAt extract was moderate against normal cells, including liver embryonic cells, kidney epithelial cells, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in recent decades, a significant number of medicinal herbs have been reported to have biofunctional effects in treating chronic liver diseases through eliminating viruses, alleviating fibrogenesis, and suppressing tumorigenesis. As a result, plant extracts can be considered as potential anti-cancer candidates for cancer therapy [ 9 , 10 ]. Here, in the first study to investigate the anti-hepatoma activity of CAt extract in vitro and in vivo, our results first found that HCC cells were inhibited by CAt extract; nevertheless, the cytotoxicity of CAt extract was moderate against normal cells, including liver embryonic cells, kidney epithelial cells, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Cedrus contains at least four species: C. deodara , C. libani , C. brevifolia , and C. atlantica . Among these, C. deodara is widely studied in regard to different biofunctions, such as anti-inflammatory [ 10 ], anti-cancer [ 11 , 12 , 13 , 14 , 15 , 16 ], anti-oxidant [ 17 ], and antimicrobial activities [ 18 , 19 ]. In terms of its anti-cancer activity, it has been shown that C. deodara extract has obvious inhibitory effects on tumor growth in various cancers such as leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that CA may inhibit growth and induce apoptosis in these aggressive cells which are prone to acquiring drug resistance. Recent studies have demonstrated that drug combinations are much more effective in cancer treatment than single molecules, with many advantages, such as reduced emergence of drug resistance being utmost important, along with increased patient survival (Lin et al, 2019; Lodi et al, 2017) and the obvious economic benefits (Karlsson, Nygren, & Glimelius, 2001; Mokhtari et al, 2017). Our finding showing growth‐inhibitory and apoptosis promoting ability of CA in TNBCs may result in additional benefits if used in combination therapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of selective, potent, and relatively non-toxic natural compounds to impede tumors and enhance chemosensitivity has gained immense importance [19]. Moreover, some natural plant products exhibit excellent in inhibiting Wnt/β-catenin signaling and improving chemosensitivity in some cancers [20].…”
Section: Introductionmentioning
confidence: 99%